Function failure and failure boundary analysis for an aircraft lock mechanism. (December 2016) - Guo, Wei; Cui, Weimin; Shi, Yu; Liu, Jingyi; Song, Bifeng
Abstract: This paper analyzes the functional principle and functional hazard analysis for a landing gear cabin door lock mechanism, concluding that the unlocking function of the lock mechanism is the one at most risk. Then the failure probability of the unlocking process of the lock mechanism is calculated, based on the simulation model of the lock mechanism and the response surface method. At last, the failure boundary of the lock mechanism is studied, including: (a) A method for the failure boundary analysis of the lock mechanism is proposed; (b) The failure boundaries respectively with single-parameter and with double-parameter are obtained based on the simulation model; (c) With the lock mechanism's assembly error taken into consideration, the failure boundary of the lock-ring position is verified through the cabin door lock system test, which is quite helpful for the maintenance and management of the aircraft lock mechanism. Highlights: Functional principle and hazard analysis of an aircraft landing gear cabin door new lock mechanism Mechanism unlocking failure probability via simulation model and response surface methods A proposed method for the lock mechanism failure boundary analysis, based on simulation and test